2018
DOI: 10.1021/acsami.8b04916
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stiff Film Pattern Geometry on Surface Buckling Instabilities of Elastic Bilayers

Abstract: Buckling instabilities-such as wrinkling and creasing-of micropatterned elastic surfaces play important roles in applications, including flexible electronics and microfluidics. In many cases, the spatial dimensions associated with the imposed pattern can compete with the natural length scale of the surface instabilities (e.g., the wrinkle wavelength), leading to a rich array of surface buckling behaviors. In this paper, we consider elastic bilayers consisting of a spatially patterned stiff film supported on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
1
24
0
1
Order By: Relevance
“…Polymeric substrates comprising local mechanical stiffness pattern or nanostructural features are intensively investigated in the context of applications such as haptic displays (touchpads), stretchable electronics, mechanical and optical data storage devices, [1][2][3][4][5][6][7][8] or as instructive cell substrates guiding mechanosensitive (stem) cells. [9][10][11][12][13][14][15] While individual cells can react to structural features of few nanometers in size and mechanical differences in the Pascal (Pa) range, [9,14] the tactile sensitivity of a human finger is only capable of detecting structural features above 10 nm and local mechanics in the kPa regime.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric substrates comprising local mechanical stiffness pattern or nanostructural features are intensively investigated in the context of applications such as haptic displays (touchpads), stretchable electronics, mechanical and optical data storage devices, [1][2][3][4][5][6][7][8] or as instructive cell substrates guiding mechanosensitive (stem) cells. [9][10][11][12][13][14][15] While individual cells can react to structural features of few nanometers in size and mechanical differences in the Pascal (Pa) range, [9,14] the tactile sensitivity of a human finger is only capable of detecting structural features above 10 nm and local mechanics in the kPa regime.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the wrinkling of large-size uniform film bonded on elastic substrate, recently, a series of studies have revealed differently post-wrinkle morphologies in systems composed of patterned stiff films on soft substrates [111][112][113][114][115][116][117][118][119]. When the length scale of the pattern is comparable to the wavelength of wrinkles, stress localization near the pattern arises under compression.…”
Section: Planar Substratesmentioning
confidence: 99%
“…When the length scale of the pattern is comparable to the wavelength of wrinkles, stress localization near the pattern arises under compression. The feature size, geometry, and spacing are all demonstrated to have important effect on the wrinkling and post-wrinkle morphologies of patterned films [ 111 , 114 , 116 , 118 ]. For example, the preformed pattern can act as novel boundary to direct surface wrinkling for controllable fabrication of hierarchical wrinkling patterns with precise orientation [ 113 , 119 ].…”
Section: Mechanics Behind the Wrinklesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several creative approaches have been demonstrated for creating patterns on soft materials 4,5 , particularly photolithography 6,7 , buckling instabilities [8][9][10] , printing 11,12 , and moulding 13,14 . Photolithography is one of the most common methods for the chemical patterning of soft material surfaces owing to its high resolution and possibility of on-demand patterning.…”
mentioning
confidence: 99%